Layanan Pendidikan Bagi Anak Gifted - Idrus, Muhammad (Universitas Ahmad Dahlan, 2013)
Many gifted children are not receiving appropriate educational services for them. By neglecting to give them the proper education which they should received, will making gifted children can not growing and developing aspects of their giftedness.Monks proposed the concept of âTriadic model of giftednessâ which proposed by Renzulli by adding elements of family, school and peers (milieu or the environment), to furnish the Renzulli concept which consists of creative, task commitment, and ability above average. Monks concepts consider the proper education for gifted children to develop their giftedness, such as special classes, accelerated classes or enrichment classes.